PENGARUH PEMBERIAN MOTIVASI DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PT SULUH DWIPANTARA - M. Iqbal Yusri,; Yusri Ilyas,; Muhaimin, Muhaimin (JOEL: Journal of Educational and Language Research, 2022)
The purpose of this study was to determine the effect of providing motivation and work experience on employee performance partially and simultaneously or together at PT Suluh Dwipantara. The sampling technique used is saturated sampling with a total sample of 33 respondents. The data used in this study were obtained using a research instrument, namely a questionnaire, then analyzed through validity testing, reliability testing, classical assumption testing, regression analysis, coefficient of determination, and hypothesis testing. The results of this study obtained the results of the regression equation Y = 12.697 + 0.726X1 + 0.250X2. In addition, based on the results of the F test, it is known that there is an effect between the variable Giving Motivation (X1) and Work Experience (X2) together on Employee Performance (Y) of 79,698 with sig. F 0.000 < 0.05. Simultaneously it is known that the variable giving motivation (????1) and work experience (????2) has an effect on employee performance (Y) with an Adjusted R – Square value of 0.938, meaning that the variable giving motivation and work experience has an influence of 93.8% on employee performance.